Simulation of performance of five types of external windows: a case study in Chongqing, China - Li, DK; Chen, JH; Lu, LD (E3S web of conferences, 2023)
The efficiency of transparent envelopes must be improved in purpose of saving energy. The EnergyPlus software was used to examine the inside glass surface temperature and annual energy performance (AEP) of five different types of external windows, including built-in louvre ventilation windows (BLVW), built-in louvre hollow windows (BLHW), interior side louvre ventilation windows (ILVW), ventilation windows (VW), and regular hollow windows (HW), using office buildings in Chongqing as the target. The results demonstrate that the design of ventilation and louvres can reduce energy consumption of buildings, lower the room's radiant asymmetry, and raise occupant thermal comfort. During the cooling season, built-in louvre ventilation windows and hollow windows for rooms facing south are the best window operation options. During the heating season, ventilation windows are the best option. In four orientations of north, east, south, and west, respectively, the overall building energy efficiency rate of the optimal operation mode compared to typical hollow windows is 5.87%, 5.70%, 2.80%, and 5.74%. This will serve as a guide for the building design of energy-efficient windows and the mode of the windows' year-round functioning in Chongqing.